Renewal of seasonally anoxic Saanich Inlet is temporally and spatially dynamic - Soetaert, Grayson; Hamme, Roberta C.; Raftery, Erinn (Frontiers in Marine Science, 2022)
Injection of oxygenated water into anoxic basins sets off a cascade of biogeochemical reactions and ecosystem shifts. The dynamic nature of these events can create spatial variability in the resulting water mass that strongly affects subsequent observations. Their irregularity can also make their prediction for experiment planning challenging. Our study focuses on Saanich Inlet, one of the most accessible and well-studied anoxic basins in the world. In the late summer and early fall, dense water can cross the sill into this fjord, in discrete events, bringing oxygen and nitrate to the deep waters of the inlet. We assess the potential strength of these renewal events using density measured at a bottom mooring on the sill. We find that the occurrence and potential strength of renewals is primarily controlled by tidal current speeds, which can be well predicted. However, the intensity of coastal upwelling, which brings dense water into the estuarine system, plays a significant secondary control, reducing predictability. We also demonstrate that renewals do not result in a homogeneous water mass filling the deep inlet. Instead, high frequency measurements from a profiling mooring in the centre of the inlet reveal that different densities intruding over the several-day renewal period create a complex layering of waters containing different proportions of new oxic and old anoxic waters. Finally, we show that not every instance of high density water observed over the sill results in flushing of the deepest waters inside the inlet. We hypothesize that each renewal improves the chance of a subsequent renewal in the same season by reducing the density contrast between waters entering and already inside the inlet. Consideration of the temporal and spatial complexity of these renewal dynamics is necessary to support studies using Saanich Inlet as a natural laboratory for exploring oxygen deficient systems.